2008
DOI: 10.1111/j.1399-3054.2008.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Size exclusion limits and lateral heterogeneity of the stomatal foliar uptake pathway for aqueous solutes and water‐suspended nanoparticles

Abstract: Penetration rates of foliar-applied polar solutes are highly variable and the underlying mechanisms are not yet fully understood. The contribution of stomata especially, is still a matter of debate. Thus, the size exclusion limits of the stomatal foliar uptake pathway, its variability and its transport capacity have been investigated. The size exclusion limits were analyzed by studying the penetration of water-suspended hydrophilic particles of two different sizes (43 nm or 1.1 microm diameter) into leaves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
302
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(325 citation statements)
references
References 39 publications
17
302
0
6
Order By: Relevance
“…The incorporation of nanoparticles into leaves has been reported earlier by Eichert et al who found that polymeric nanoparticles penetrated into the epidermis of Vicia faba (21). Corredor et al found nanoparticle penetration into the first cell layer of pumpkin plants (20).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The incorporation of nanoparticles into leaves has been reported earlier by Eichert et al who found that polymeric nanoparticles penetrated into the epidermis of Vicia faba (21). Corredor et al found nanoparticle penetration into the first cell layer of pumpkin plants (20).…”
Section: Discussionmentioning
confidence: 61%
“…Increasing the thickness of the biological barrier will therefore reduce the mobility of the nanoparticles and consequentially their ability for translocation. Uptake of nanoparticles into plant leaves has been proposed to occur through small pores in the cuticle (< 5 nm) or through stomatal apertures (21). Cell wall pores are smaller than ten nanometers and the cell wall is expected to be a tight sieve which does not allow nanoparticles migration (34).…”
Section: Translocation Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of epidermal structures in plant surfaces such as lenticels, stomata or trichomes may significantly influence the rate of absorption of surface-applied agrochemicals. While the significance of the stomatal pathway on the absorption of foliar sprays has been a matter of controversy for many years, recent evidence shows that it can largely contribute to the uptake process (Eichert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ENMs have the potential to penetrate leaf surfaces through stomatal pores (Eichert et al, 2008;Larue et al, 2014). Basipetal translocation of carbon-coated iron nanoparticles was evident from the epidermis of exposed Cucurbita mixta petioles; similarly, Ce was found in Cucumis sativus roots after leaf exposure to nanoparticulate CeO 2 (Corredor et al, 2009;Hong et al, 2014).…”
Section: Foliar Uptakementioning
confidence: 86%